Let
S = β = 1 ∑ 2 0 α = 1 ∑ 2 0 tan − 1 ( β α ) .
Evaluate π S .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Important Identity for this problem:
tan − 1 b a + tan − 1 a b = 2 π
(I have denoted α by a and β by b in this solution)
There will be a total of 20×20=400 terms
For every b a term there will be a a b term, except when a = b . Addition of those two terms will give us π/2 for every pair.
There are 20 terms where a = b , and 380 other terms. Thus, the total number of pairs that will give 2 π is 2 3 8 0 = 1 9 0 .
The other 20 terms will each have a = b , and tan − 1 1 = 4 π
Therefore, the answer is 1 9 0 ⋅ 2 π + 2 0 ⋅ 4 π = 1 0 0 π
Problem Loading...
Note Loading...
Set Loading...
S = β = 1 ∑ 2 0 α = 1 ∑ 2 0 tan − 1 ( β α ) = 2 1 ⎝ ⎛ β = 1 ∑ 2 0 α = 1 ∑ 2 0 tan − 1 ( β α ) + α = 1 ∑ 2 0 β = 1 ∑ 2 0 tan − 1 ( α β ) ⎠ ⎞ = 2 1 ⎝ ⎛ β = 1 ∑ 2 0 α = 1 ∑ 2 0 tan − 1 ( β α ) + β = 1 ∑ 2 0 α = 1 ∑ 2 0 tan − 1 ( α β ) ⎠ ⎞ = 2 1 β = 1 ∑ 2 0 α = 1 ∑ 2 0 ( tan − 1 ( β α ) + tan − 1 ( α β ) ) = 2 1 β = 1 ∑ 2 0 α = 1 ∑ 2 0 ( tan − 1 ( β α ) + cot − 1 ( β α ) ) = 2 1 β = 1 ∑ 2 0 α = 1 ∑ 2 0 ( tan − 1 ( β α ) + 2 π − tan − 1 ( β α ) ) = 2 1 β = 1 ∑ 2 0 α = 1 ∑ 2 0 2 π = 2 2 0 × 2 0 × 2 π = 1 0 0 π Add another S with α and β swapped. Swapped and order of summation.
Therefore, π S = 1 0 0 .